Total synthesis of twelve membered resorcyclic acid lactones, (R)-penicimenolide A, (R)-resorcyclide and (R)-dihydroresorcyclide - Das, Pronay; Reddy, D. Srinivasa (Tetrahedron, 2021)
Resorcyclic Acid Lactones or RALs are a class of fungal secondary polyketides isolated from a variety of fungal strains like Lasiodiplodia theobromae, Penicillium sp., Syncephalastrum racemosum etc. This class of macrocyclic lactones are found to exhibit a broad spectrum of biological activities and are of significant synthetic importance. Herein, we report the first total synthesis of (R)-penicimenolide A, twelve membered RAL (RAL12) isolated from Penicillium sp. (NO. SYP-F-7919). Besides, we also report the total synthesis of two other members, namely, (R)-trans-resorcyclide and (R)-dihydroresorcyclide. In the course of synthesis, we have utilized ring closing metathesis (RCM) as the key step in constructing the core macrolactone scaffold. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Macrocycle; Natural product; organic synthesis; Total synthesis

Studies directed toward the total synthesis of nannocystin A - Nomula, Rajesh; Pratapure, Madhukar S.; Kontham, Ravindar (ChemistrySelect, 2022)
A full account of our efforts directed toward the stereoselective total synthesis of nannocystin A, a macrocyclic myxobacterial metabolite, is presented. In this endeavor, we have attempted two distinct synthetic routes to access polyketide fragment (C1-C11) of macrocyclic depsipeptide (21-membered) natural product from readily accessible building blocks 1,3-propanediol and benzaldehyde employing Evans aldol, CBS reduction, Heck cross-coupling, and Sharpless asymmetric epoxidation as key transformations. Ultimately, accomplished the synthesis of the complete skeleton (21-membered precursor for macrocyclic depsipeptide) of the nannocystin A possessing desired stereochemistry and functional groups.
Keywords: amidation; Depsipeptide; Evans aldol reaction; Macrocycle; Nannocystins

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene